Analysis of the Influence of Organizational Culture and Employee Competency on Service Satisfaction at the General Secretariat of the State Police of the Republic of Indonesia (POLRI ) - Bondan Suandaru; Zulkifli Rangkuti; Nurwulan Kusuma Devi (Dinasti Publisher, 2026)
This study aims to analyze the influence of organizational culture and employee competency on service satisfaction at the Indonesian National Police General Secretariat . The background of the study is based on the demand for improving the quality of reliable, modern, and information technology-based public administration services, which in practice still face obstacles in the form of suboptimal internalization of organizational culture and limited employee competency. This study uses a quantitative approach with a survey method. The research population is employees at the Indonesian National Police General Secretariat, with data collected through a structured questionnaire. Data analysis techniques include validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results of the study indicate that organizational culture has a positive and significant effect on service satisfaction. Employee competence also has a positive and significant effect on service satisfaction. Simultaneously, organizational culture and employee competence significantly influence service satisfaction at the Indonesian National Police General Secretariat. These findings confirm that strengthening consistent work culture values and improving employee competence, both in terms of knowledge, skills, and work attitudes, are important factors in supporting the improvement of the quality of professional, prompt, and accountable public administration services. This research is expected to provide academic contributions in the development of public sector human resource management studies, as well as practical contributions as a basis for formulating policies to strengthen organizational culture and develop employee competencies within the Indonesian National Police General Secretariat.